GREAT POTENTIAL BUT LITTLE IMPACT: THE EUROPEAN UNION’S PROTECTION POLICIES FOR THE BALTIC SEA - Schumacher, Tom (Baltic Journal of Political Science, 2012)
Since the completion of the Eastern enlargement in 2004, a major responsibility for addressing the Baltic Sea pollution lies with the European Union. It provides strong institutions to facilitate environmental decision-making and to enforce the implementation of regulations. However, the measures taken so far have not been sufficient to significantly improve the state of the Baltic Sea. In particular, the Common Agricultural Policy does not take the ecological characteristics of the region into consideration. Instead, it provides false incentives since it generally encourages farmers to increase production and to extend areas under cultivation. To enhance the EU’s role, it is crucial to raise the awareness of the Baltic Sea’s vulnerability in Brussels. Moreover, European regulations and policies should become more flexible and match the regional specific environmental requirements. At the same time, too heavy financial burdens and distortions of competition, especially for the region’s agricultural sector, should be avoided.